2011
DOI: 10.2138/am.2011.3689
|View full text |Cite
|
Sign up to set email alerts
|

A first-principles study of the phase transition from Holl-I to Holl-II in the composition KAlSi3O8

Abstract: The phase relation and structural evolution of Holl-I and Holl-II in the composition KAlSi 3 O 8 at 0 K have been investigated by the first-principles method up to 130 GPa. Holl-I and Holl-II are polymorphs of KAlSi 3 O 8 stable at low pressures and high pressures, respectively. The transition pressure is determined at ∼23(5) GPa, in agreement with recent experimental observations. All experimentally observed major changes associated with this phase transition such as the deviation of the γ-angle from 90°, spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Compared to the experimentally-determined curves, the curve obtained with the GGA method has a slightly steeper slope whereas that obtained with the LDA method has a more gradual slope. In general, the GGA method should yield a lower K T and the LDA method should yield a higher K T , with the experimentally-constrained K T falling in between (Deng et al, 2011). The V/V 0 -P trend from Nestola et al (2014) is much closer to our GGA result, while the V/V 0 -P trend from Yong et al (2012) is much closer to our LDA result.…”
Section: Resultssupporting
confidence: 67%
“…Compared to the experimentally-determined curves, the curve obtained with the GGA method has a slightly steeper slope whereas that obtained with the LDA method has a more gradual slope. In general, the GGA method should yield a lower K T and the LDA method should yield a higher K T , with the experimentally-constrained K T falling in between (Deng et al, 2011). The V/V 0 -P trend from Nestola et al (2014) is much closer to our GGA result, while the V/V 0 -P trend from Yong et al (2012) is much closer to our LDA result.…”
Section: Resultssupporting
confidence: 67%
“…In view of the disordered site occupation between Al and Si, two models with and without tetragonal symmetry were considered in our simulations. Model A (Figure a) applying the tetragonal symmetry was selected from the previous work of Kawai and Tsuchiya [] and Model B (Figure S1a) without tetragonal symmetry from the work of Deng et al [].…”
Section: Methodsmentioning
confidence: 99%
“…Previous calculations on K‐hollandite investigated its equation of states, elasticity, and phase transition from a tetragonal (hollandite I) to a monoclinic phase (hollandite II) [ Mookherjee and Steinle‐Neumann , ; Caracas and Ballaran , ; Mussi et al , ; Deng et al , ; Kawai and Tsuchiya , ]. The latter revealed that K‐hollandite exhibits strong shear wave anisotropy at high pressure, and [001] dislocations are favored under the shear stress of the subducted slabs [ Mussi et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Many high‐ P studies with different methods have been conducted to disclose the high‐ P behavior of feldspar [e.g., Ringwood et al , 1967; Liu , 1978; Yagi et al , 1994; Gautron et al , 1996; Akaogi et al , 2004a; Sueda et al , 2004; Nishiyama et al , 2005; Liu , 2006; Hirao et al , 2008; Mookherjee and Steinle‐Neumann , 2009; Deng et al , 2010, 2011], and significant progress has been achieved. As summarized in Liu et al [2010a], Ab (NaAlSi 3 O 8 ) breaks down to jadeite (Jd; NaAlSi 2 O 6 ) + Qtz at ∼2.5 GPa [ Birch and LeComte , 1960; Liu , 1978; Holland , 1980], which in turn transforms into Jd + Coe at ∼3 GPa, then into Jd + St at ∼9 GPa and finally into calcium ferrite‐structured NaAlSiO 4 (CF) + St at ∼22 GPa [ Liu , 1978; Yagi et al , 1994; Tutti et al , 2000; Deng et al , 2010].…”
Section: Introductionmentioning
confidence: 99%
“…At approximately 10 GPa, these three phases, Wd, Ky and St, recombine to form a hollandite‐type phase with the composition of KAlSi 3 O 8 (Holl‐I). At ∼23 GPa, the structure of Holl‐I is deformed and an isochemical new phase forms (Holl‐II) [ Sueda et al , 2004; Nishiyama et al , 2005; Ferroir et al , 2006; Deng et al , 2011]. Compared to the density of the mantle material at similar pressures, the density of the isochemical phase assemblages of San and Wd + Ky + Coe is generally low, that of the phase assemblages of Wd + Ky + St and Holl‐I relatively high, and that of Holl‐II broadly similar.…”
Section: Introductionmentioning
confidence: 99%